Identifikasi Ketebalan Lapisan Lapuk Pada Zona Rawan Longsor Menggunakan Metode Geolistrik Tahanan Jenis (Studi Kasus: Ruas Jalan Kolaka-Kolaka Timur) - triani, triani; Kamur, Sudarwin; Kusmita, Tri; Ningsih, Surya; Desiasni, Rita (Jurnal Riset Fisika Indonesia, 2025)
The Kolaka-Kolaka Timur road section serves as a vital connection among several districts in Southeast Sulawesi. This region is particularly susceptible to landslides during the rainy season, resulting in the road being obstructed by landslide debris. The objective of this research is to assess the thickness of the weathered layer, a critical factor contributing to landslides, as part of efforts aimed at mitigating such events. The research employs the resistivity geoelectric method utilizing a Wenner configuration with five passes. The electrode spacing is set at 7 meters, covering a total track length of 105 meters. Analysis of the measurement results indicates that the weathered layer across each track comprises alluvial deposits originating from the weathering of Sekis rocks, characterized by a resistivity of less than 20 Ωm. The thickness of the weathered layer varies across the tracks: Track 1 exhibits a thickness ranging from 4 to 12 meters, Track 2 ranges from 1 to 10 meters, Track 4 varies from 0 to 8 meters, and Track 5 shows a thickness between 0 and 10 meters.